2008
DOI: 10.1007/s00467-007-0707-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum calcium values in term and late-preterm neonates receiving gentamicin

Abstract: Since noting an apparent increase in hypocalcemia in neonates receiving gentamicin every 24 h (q 24 h) for > or = 4 days, we have prospectively monitored serum calcium (Ca) values in these patients receiving prolonged gentamicin therapy. This study is a retrospective analysis of those values measured during gentamicin treatment. The study included neonates with gestational age > or = 35 weeks who received > or = 4 days of gentamicin therapy and in whom at least one serum Ca value was measured > or = 47 h after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Indeed, a cumulative effect of gentamicin was observed. [10][11][12] We found an increase in urinary calcium excretion after the first dose of gentamicin, and an even higher increase after the second dose of gentamicin. A previous study showed that serum calcium levels were lowest on third day of gentamicin.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Indeed, a cumulative effect of gentamicin was observed. [10][11][12] We found an increase in urinary calcium excretion after the first dose of gentamicin, and an even higher increase after the second dose of gentamicin. A previous study showed that serum calcium levels were lowest on third day of gentamicin.…”
Section: Discussionmentioning
confidence: 60%
“…1,2 Some studies in newborns and animals have shown that gentamicin increases urinary calcium excretion. [11][12][13][14][15] Injection every 36-48 hours is a new recommendation for intravenous gentamicin treatment in newborns. 3 Following this new recommendation, there have been no further studies on the effects of extended gentamicin dosage on urinary calcium excretion in newborns.…”
Section: G Entamicin Is a Common First-line Antibiotic Therapy For Inmentioning
confidence: 99%
“…Vitamin D de ciency was de ned as serum 25(OH) vitamin D < 10 ng/ml, insu ciency 10-30 ng/ml and su ciency > 30 ng/ml, respectively (17,18). Serum Calcium < 8 mg/dL was also considered as hypocalcemia (19)…”
Section: Methodsmentioning
confidence: 99%
“…Administration of aminoglycosides, in particular gentamicin, to neonates, is also associated with a drop in calcemia (12)(13). This could be explained by the fact that aminoglycoside antibiotics are CaSR agonists (14)(15).…”
Section: Introductionmentioning
confidence: 99%